2020
DOI: 10.1155/2020/8412957
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Social Health Insurance and Associated Factors among Health Care Providers in Addis Ababa, Ethiopia

Abstract: Background. Cost sharing between beneficiaries and government is critical to attain universal health coverage. The government of Ethiopia introduced social health insurance to improve access to quality health services. Hence, HCP are the ultimate frontline service provider; their WTP for health insurance could influence the implementation of the scheme directly or indirectly. However, there is limited evidence on willingness to pay (WTP) for social health insurance (SHI) among health professionals. Methods. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 11 publications
9
29
2
Order By: Relevance
“…This could be due to the difference in socio-demographic characteristics of study participants. But this study finding was slightly higher than other studies done in Ethiopia, Tigray region (35.5%) [ 24 ], and Addis Ababa city (28.7%, 17%) [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This could be due to the difference in socio-demographic characteristics of study participants. But this study finding was slightly higher than other studies done in Ethiopia, Tigray region (35.5%) [ 24 ], and Addis Ababa city (28.7%, 17%) [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 84%
“…This maybe due to their medical cost being already covered and they consider it as extra cost [ 19 , 20 ]. This study might be also due to their higher income from other sources, which makes them able to cover their medical expense OOP money and by other sources [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…‘Ability to pay’ (ATP) and ‘willingness to pay’ (WTP) are economic concepts that have wide use in the valuation of healthcare [ 8 , 9 ]. In recent years, both ATP and WTP have been studied in a variety of low- and middle-income countries who are introducing a form a social health insurance, including Ghana, Nigeria, Laos, Pakistan, Ethiopia and Uganda [ 10 16 ]. A comparative study hasn’t been performed in Indonesia, where JKN constitutes the largest social health insurance programme in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of these studies report a high rate of willingness to willingness to participate and pay for health insurance, ranging from (25,(27)(28)(29). However, there are also studies reporting low willingness to pay among respondents (30,31). Similarly a study carried out among health professionals in Ethiopia reported a 28.7% willingness to participate rate (31).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also studies reporting low willingness to pay among respondents (30,31). Similarly a study carried out among health professionals in Ethiopia reported a 28.7% willingness to participate rate (31).…”
Section: Introductionmentioning
confidence: 99%